Study of Ship Accident Factors and Ship Routes Correlation - Iskandar, S.; Hasugian, S.; Fatimah, S. (Scientific Journal of Gdynia Maritime University, 2018)
The sailing safety was a very important issue that had to be solved in Indonesia. There were accidents causing victims and material losses caused by ship operator’s ignorance and less awareness on safety. The ship operator was responsible for technical matters and to guide human resources. The aim was to map the correlation between ship accident causes and particular routes. The research used the Pearson Product Moment correlation trial to map correlation between accident events to particular routes. The data used was decision report of shipping court published in 2015–2016. Then, the causes were grouped and the result showed that human factor is the main factor of accident. The accident factor had the high correlation with the location where the accident happened.